2018
DOI: 10.1108/jhlscm-11-2017-0066
|View full text |Cite
|
Sign up to set email alerts
|

Emergency evacuation planning in natural disasters under diverse population and fleet characteristics

Abstract: Purpose The purpose of this paper is to formulate and solve a new emergency evacuation planning problem. This problem addresses the needs of both able and disabled persons who are evacuated from multiple pick-up locations and transported using a heterogeneous fleet of vehicles. Design/methodology/approach The problem is formulated using a mixed integer linear programming model and solved using a heuristic algorithm. The authors analyze the selected heuristic with respect to key parameters and use it to addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Logistics and supply chain management are both crucial to supporting the timely response of an HO to a disaster (Chong et al, 2019). By definition the disaster is likely to occur suddenly, without warning, with devastating consequences affecting a wide area and potentially a large number of victims (Cozzolino, 2012;Baou et al, 2018). HLSCM is a distinctive unit of any HO, and the success or failure of any humanitarian operation is highly dependent on this unit (Cozzolino, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Logistics and supply chain management are both crucial to supporting the timely response of an HO to a disaster (Chong et al, 2019). By definition the disaster is likely to occur suddenly, without warning, with devastating consequences affecting a wide area and potentially a large number of victims (Cozzolino, 2012;Baou et al, 2018). HLSCM is a distinctive unit of any HO, and the success or failure of any humanitarian operation is highly dependent on this unit (Cozzolino, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that the minimization of travel time for an evacuation plan should not be the only objective for a planner, especially when the capacity and street traffic play critical variables in the problem. Baou et al [12] proposed a model to consider the disabled population in the evacuation plan. They found that evacuating people with disabilities has a significant impact on total evacuation time.…”
Section: Methodsmentioning
confidence: 99%
“…In [126], the problem of evacuating evacuees with disabilities is addressed based on their categories by a fleet of heterogeneous vehicles. Here, the vehicle ranged from ambulances, vehicles that are capable of carrying only normal evacuees, as well as vehicles for carrying evacuees with wheelchairs.…”
Section: Heuristics and Local Search In Evacuation Vrpsmentioning
confidence: 99%
“…From these models, various interesting and complex problems are addressed. As a general trend, it could be seen that most work addressed split delivery, such as in [34,42,46,47,[49][50][51]61,71,73,75,76,78,81,83,85,87,94,96,102,116,123,128,158] and multi-trip VRP that can be seen in [31,47,50,61,76,88,90,94,97,98,124,126,129], ref. [134,149,159] normally stressed on the problem of vehicle limitations such as the numbers of vehicle or the fuel limitation.…”
Section: Current Trendsmentioning
confidence: 99%
See 1 more Smart Citation